Management of pregnancy in case of multiple and giant uterine fibroids. Issue 11 (3rd November 2020) - Reis-de-Carvalho, Catarina; Lopes, João; Henriques, Alexandra; Clode, Nuno
Abstract : Uterine fibroids are common among women of reproductive age. During the pregnancy, the potential complications of fibroids, although rare, are of frequent clinical concern. Available studies describing management and obstetrical outcomes in pregnant women with giant fibroids are limited. We present the case of a 39-year-old pregnant woman with multiple and large uterine fibroids. During the pregnancy, there was adequate fetal development, without major maternal complications. Given the characteristics of the fibroids and breech position of the fetus, an elective caesarean section was decided, and postpartum hysterectomy planned. This challenging obstetrical case required a multidisciplinary approach. We considered crucial discussing five main issues: preconceptional counselling, tailored pregnancy surveillance, decision of time and route of delivery, decision to perform a peripartum hysterectomy and management of decreasing blood loss perioperatively. Given the limitation of the published reports, we believe that sharing our experience, along with a literature review, is beneficial for other clinicians.